Education or Exotification?: A Reexamination of the Smithsonian Folklife Festival - Kelly J Schultz (The Journal of Undergraduate Research, 2011)
<!--[if gte mso 9]> 72 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> As a central cultural event and meeting grounds for the diverse cultures of the United States, the Smithsonian Folklife Festival has a significant influence on the cultural education and intergroup understanding. The Festival has been a central case study in some of the central debates of Folklore: exotification, authenticity, traditionalism, presentation, and representation. In this study, I examine some of the key publications involved in the debate and reconsider their arguments in terms first person experience as an intern at the 2010 Festival, textual data, and ethnographic interview with Festival staff, curators, and participants. I conclude that these issues not yet resolved, pose some degree of risk to public good, and require further attention from Festival developers.